2020
DOI: 10.1002/htj.21798
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thermal characteristics of square wavy plates

Abstract: In this paper, the thermal characteristics and air flow behavior over heated square plate of wavy configurations are assessed. Two cases of heated wavy configurations were considered, one having an elliptical and other with the sinusoidal cross‐sectional shape to augment heat transfer rate over the plate. To explore the impact of wavy configurations of plate on convective heat transfer, the Rayleigh numbers in the range of 104 to 1013 were considered. The steady‐state two‐dimensional momentum and energy equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Through the numerical study of natural convection heat transfer on isothermal horizontal plates with triangular corrugations (continuous and spaced), Oosthuizen and Kalendar (2020) concluded that the inclusion of triangular corrugations, compared to the flat plate geometry, always increases the heat transfer rates, with a greater increase observed in geometries with spaced corrugations. Hussain et al (2020) numerically studied the natural convection in square horizontal plates with different types of elliptical and sinusoidal corrugations and in isothermal heating conditions. They concluded, in comparison to the flat plate geometry, that using corrugations increases the heat transfer rates (with greater increases observed in sinusoidal corrugations).…”
Section: Hff 339mentioning
confidence: 99%
“…Through the numerical study of natural convection heat transfer on isothermal horizontal plates with triangular corrugations (continuous and spaced), Oosthuizen and Kalendar (2020) concluded that the inclusion of triangular corrugations, compared to the flat plate geometry, always increases the heat transfer rates, with a greater increase observed in geometries with spaced corrugations. Hussain et al (2020) numerically studied the natural convection in square horizontal plates with different types of elliptical and sinusoidal corrugations and in isothermal heating conditions. They concluded, in comparison to the flat plate geometry, that using corrugations increases the heat transfer rates (with greater increases observed in sinusoidal corrugations).…”
Section: Hff 339mentioning
confidence: 99%
“…Two different heat fluxes were tested: Qwall = 1 × 10 5 Wm −2 and Qwall = 1 × 10 6 Wm −2 , resulting in Rayleigh numbers of Ra = 3.8 × 10 4 and Ra = 3.8 × 10 5 , respectively. Unlike previous works [5][6][7][8][9], we specifically address the transient regime, which can be most relevant for heat exchangers operating under real cooling conditions. For example an electronic device can be refrigerated by a tested surfaces in a submerged application.…”
Section: Geometry Impact On Natural Convection With Imposed Heat Fluxmentioning
confidence: 99%
“…Various methods employed for this purpose involve surface modifications, such as adding fins or utilizing small cavities or grooves. Several studies found in the literature [5][6][7][8][9] investigate the impact of surface modifications on enhancing free convection heat transfer processes. Generally, these studies examine surface modifications with configurations resembling waves, employing sinusoidal functions [10,11], evenly spaced geometries like triangular [8,12] or squared [9,13] patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the use of corrugated plates, especially based on the conclusion of Oosthuizen and Garrett (2001), is a promising alternative for the optimization of cooling systems by natural convection, thereby motivating new research in the area. Also noteworthy are the numerical studies by Oosthuizen (2016a); Oosthuizen (2016b; Gibanov and Sheremet (2017); Gibanov and Sheremet (2019); Oosthuizen and Kalendar (2020); Hussain et al (2020) on the use of corrugated plates to improve natural convection heat transfer rates.…”
Section: Introductionmentioning
confidence: 99%